Issue Information. Issue 2 (February 2016) - Unknown
Abstract : Cover Illustration In vivo fluorescence correlation spectroscopy analyses of FMBP‐1, a silkworm transcription factor. From M. Tsutsumi et al. (pp.106–125 ).